Comparison of Conventional Economic Theory with Islamic Economic Thought - Royani; Yadi Janwari; Ahmad Hasan Ridwan (al-Afkar, Journal For Islamic Studies, 2023)
In this abstract, we will compare conventional economic theory with Islamic economic thought. Conventional economics is based on the principles of liberal capitalism which focuses on economic growth, resource allocation and individual profit. On the other hand, Islamic economic thought is based on Islamic religious teachings and ethical principles that involve justice, sustainability, and social welfare. One of the main differences between traditional (conventional) economic theory and Islamic economic thought lies in the perspective of economic resources. In a traditional economy, resources are treated as belonging to individuals or companies seeking to maximize private profit. On the other hand, Islamic economic thought emphasizes shared ownership and social responsibility in resource management. This research is descriptive-analytic in nature because this research was conducted to find data as accurate and complete as possible about the correlation between conventional theory and Islamic economic thinking.